Consensus statement: patient safety, healthcare-associated infections and hospital environmental surfaces. (October 2015) - Roques, Christine; Al Mousa, Haifaa; Duse, Adriano; Gallagher, Rose; Koburger, Torsten; Lingaas, Egil; Petrosillo, Nicola; Škrlin, Jasenka
Healthcare-associated infections have serious implications for both patients and hospitals. Environmental surface contamination is the key to transmission of nosocomial pathogens. Routine manual cleaning and disinfection eliminates visible soil and reduces environmental bioburden and risk of transmission, but may not address some surface contamination. Automated area decontamination technologies achieve more consistent and pervasive disinfection than manual methods, but it is challenging to demonstrate their efficacy within a randomized trial of the multiple interventions required to reduce healthcare-associated infection rates. Until data from multicenter observational studies are available, automated area decontamination technologies should be an adjunct to manual cleaning and disinfection within a total, multi-layered system and risk-based approach designed to control environmental pathogens and promote patient safety.